LEADERSHIP, BUSINESS SCHOOLS AND FINANCIAL CRISES: THE SEARCH FOR A MISSING LINK - Khan, Dr Ashfaq; Ahmad, Dr Wiqar (The journal of contemporary issues in business and government, 2013)
Business schools produce leaders who command ‘power’ and ‘governmentality’, as per Foucault’s theoretical conceptualisations, to institutionalise routines and social practices in contemporary organisations. These leaders must uphold ethics in their business decisions; however, this has not been reflected in many instances, as recurring financial crises have depicted over time. Ettorts to address the issue and reach its root cause have failed to deliver concrete results so far, which necessitates an objective probe into today’s business education. This conceptual-cum- analytical paper proposes an alternate, indirect approach to ettectively tackle the issue. We suggest two remedies: first, transformative teaching and learning activities that inculcate ethical values into students should be implemented at the grass root level – primary and secondary schools, that feed into business schools with future business leaders; second, a conducive corporate governance environment within business organisations that supports ethical decisions and nurtures ethical behaviour needs to be developed – arguably the first being the prerequisite for the second.